Anti-Ethnic Hegemony, Identity Construction and Political Complicities. Issue 3 (2nd October 2022) - Drousioti, Kalli
Abstract: Teaching material and textbooks undoubtedly operate politically and should be scrutinized concerning the knowledge that they construct and legitimize. But such scrutiny often involves new hegemonies and political complicities that also require further scrutiny. Following Ernesto Laclau and Chantal Mouffe's discourse analysis the present article critiques one such hegemony: that which sets civic identity against ethnic identity and, to prioritize the former, depoliticizes or even effaces the latter. To illustrate the need for further scrutiny of such politics the article carries out a deconstructive reading of a text (that of Yannis Papadakis, 2008 ) that is representative of this hegemony. This reading reveals that Papadakis tacitly blames ethnic identity as such for the wrongful treatment of Otherness, thus incriminating ethnic attachment wholesale and, therefore the very Otherness in whose name he purportedly deploys his social constructionism. I argue that Papadakis' modernist suggestion to disconnect the present from the historical past undermines ethnicity while failing to stave off essentialist and racial understandings of it. At cross-purposes with social constructionism, Papadakis' critique of the pernicious political operations of ethnic identities ends up annihilating ethnic identities.